Local governments and the sustainable integration of refugees in Ethiopia - Eva Binkert; Merlin Flaig; Lukas Frucht; Jörn Grävingholt; Jannis König; Jana Kuhnt; Philipp Lendle; Abdirahman A. Muhumad; Katharina Potinius (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Ethiopia is the second largest refugee-hosting country in Africa; it accommodates around 700,000 refugees, mostly from neighbouring countries. Humanitarian and development actors are increasingly highlighting the local integration of refugees as a durable solution to protracted refugee situations. Hosting states are called upon to include refugees in their national public services, rather than to sustain a parallel (humanitarian) system, and to empower refugees to secure their own livelihoods as part of the local community. The international community has endorsed this idea by adopting the Comprehensive Refugee Response Framework (CRRF) and vowing financial support. Ethiopia is one of the pilot countries implementing this framework. However, the execution of the ambitious approach faces many challenges. This paper focusses on the role of local governments within the CRRF implementation process; they have not yet been the focus of attention even though sustainable solutions largely depend on them. Results show that the CRRF implementation process has slowed down considerably in the past years, mostly remaining on a project base. Shifting political priorities, a lack of leadership and coordination at the national level as well as the unclear role and low capacities of local governments are major barriers to the local integration of refugees.
Keywords: 330